Online sexism in the German-speaking Twitter community - Yen, Jacqueline Fong Tze; Mohd Jalis, Farhana Muslim; Omar, Noritah (Silpakorn University, 2024)
The impact of movements that gain momentum worldwide by virtue of hashtags, such as #MeToo, varies across countries owing to linguistic and cultural differences, among others. Nevertheless, online sexism remains a pervasive issue, particularly on social media platforms. This study aimed to examine the prevalence of online sexism in the German-speaking Twitter community based on the hashtag #sexismus from 2020 to 2022 andcategorize and analyze the various forms of online sexism in regard to #sexismus during the same period. Employing a mixed-method approach, this study collected and analyzed 8,242 relevant tweets of #sexismus, utilizing quantitative analysis to track tweet volume trends and qualitative thematic analysis to categorize the content into seven key themes: criticism on sexism, calls for changes and actions, personal experiences of sexism and sexual harassment, LGBTQ+, movements related, media representation, and no specification possible. Key findings reveal fluctuations in tweet volume within the criticism on sexism frame, with peaks in early 2022, and highlight that the most prevalent themes included sexism in the media (28% of tweets), sexism at work (19%), and patriarchy (15%). The results suggest that while online activism against sexism exists in the German-speaking community, audience engagement varies over time and across topics. This underscores the need for dedicated efforts to address sexism in various contexts, including media, workplaces, and broader societal structures.